Litter Size and Birth Weight of Sapera Goat Kids Across Lactation Periods at Merapi Farm - Aria Fatah Mukti Satriaji; Sari Eko Tuswati; Wida Nurnaningsih; Doso Sarwanto (MEDIA PETERNAKAN, 2026)
This study evaluated whether the lactation period affects litter size and kid birth weight of Sapera goats under a semi-intensive farm system in Yogyakarta, Indonesia. Eighteen Sapera does were grouped according to lactation period: first (P1), second (P2), and third lactation (P3), with six does per group. Primary data were obtained from kidding observations, litter-size records, and kid birth weights measured within 24 h after birth; secondary data on lactation period were collected from farm records. The study used a survey approach with purposive sampling, and data were analyzed by one-way analysis of variance for a completely randomized design. Mean litter size increased numerically from 1.33 kids/doe in P1 to 1.66 in P2 and 1.83 in P3, while birth weight increased from 3.17 kg to 3.40 and 3.44 kg, respectively. However, the lactation period did not significantly affect either trait (P > 0.05). These findings indicate that the lactation period alone is insufficient as a selection criterion; complete recording of parity, body weight, nutrition, and kidding type is recommended